PERTUMBUHAN VIGNA RADIATA (L.) WIL ZEK PADA TINGKAT SALINITAS NACL YANG BERBEDA - Srie Juli Rachmawatie Mochammad Nasir (AGRONOMIKA, 2014)
Vigna radiate (L.) Wilezek is a natrophobic plant i.e. plants which are sensitive to salinity. The ain of the research was to investigate the plant growth in Vigna radiata (L.) grown in different levels of NaCl salinity.A greenhouse experiment and factorial completely randomized design was used in this study. The first factor was five levels of NaCl salinity i.e. S = g/L; S = g/L; S = g/L; S = g/L; S = g/L. The second factor is four variety of Vigna radiata L., i.e. V = var. Gelatik; V = var No. ; V = var. Parkit; V = var. Kenari. Five replication were made for treatment. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test at % significance levels and correlation analysis. The result showed that the plant growth significantly inhibited by increasing concentration of NaCl. The increase of concentration of NaCl significantly reduced plant height, total leaf area, root length, fresh weight and dry weight.